Improvement of beef cattle through breeding methods. - Smith, W.H.; Smith, E.F.; Ibsen, H.L. (Kansas Agricultural Experiment Station, 2012)
A National Beef Cattle Breeding Research Program has been initiated and is organized in three areas which are referred to as the Western, Southern, and North Central Regions in the United States. The Kansas Agricultural Experiment Station is co-operating with 12 other states in the North Central Region. The purebred Shorthorn herd maintained at Manhattan is being used as the primary basis for the purebred cattle breeding investigations conducted by the Kansas Station.
Keywords: Beef; Breeding; Performance